y-8=-x-y

Simple and best practice solution for y-8=-x-y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-8=-x-y equation:


Simplifying
y + -8 = -1x + -1y

Reorder the terms:
-8 + y = -1x + -1y

Solving
-8 + y = -1x + -1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add 'y' to each side of the equation.
-8 + y + y = -1x + -1y + y

Combine like terms: y + y = 2y
-8 + 2y = -1x + -1y + y

Combine like terms: -1y + y = 0
-8 + 2y = -1x + 0
-8 + 2y = -1x

Add '8' to each side of the equation.
-8 + 8 + 2y = 8 + -1x

Combine like terms: -8 + 8 = 0
0 + 2y = 8 + -1x
2y = 8 + -1x

Divide each side by '2'.
y = 4 + -0.5x

Simplifying
y = 4 + -0.5x

See similar equations:

| 3ln(2)=ln(8) | | t/11=11 | | -1=1/3v | | r^2-4r+6=0 | | 2a+3c-8c+5a= | | 9-8x-7-4x=5 | | 5(4x+9)-6x=8x+12 | | 253+c=-24 | | 16j-4= | | (4x-2)(3x-4)=9 | | (-a-7b+6)7ab= | | .31=log(x) | | 7+x-3x=29 | | 34-3x=9-8x | | 8(y-2)+8=3(y-4)-2 | | 4x-3(7-x)=7 | | (2xy^2+2y)dx+(2x^2y+2x)dy=0 | | 3x-72-2x=35 | | h=-t^2+2t | | x-429.30=120.44 | | 17.6n-17.28=21.8n-41.8 | | -[3x-(2x+2)]=-5-[3(2x-4)-3x] | | ln(x+4)-ln(x-2)=2 | | 3x+30+27y=0 | | -6(w+1)-w-12=-7(w+4)+10 | | -3(a+8)=a+2(5a-7) | | 20+5x=150 | | 4m+45=61+2m | | I=Crt | | 4-5x=39 | | 4s+20=200 | | -10p-5(4-4p)=6(p-2)-16 |

Equations solver categories